دور المکتبات الجامعیة المصریة فى دعم القوى الناعمة : مکتبة کلیة الهندسة جامعة عین شمس نموذجا - د. نجوى شکرى یمنى (المجلة الدولية لعلوم المكتبات والمعلومات)
This current research paper 's purpose is to spotlight the role of Egyptianuniversities' libraries in supporting the soft power which is reflected andpresented in Faculty of Engineering's library as a model. The research seeksexposing the concept of the soft power and its most important constituents ineducation through manifesting the role of Faculty of Engineering's library insupporting scientific research. Consequently, this will assist developing the softpower through the nature of the faculty's buildings, site, equipments, themanagerial subsidiarity and dependence, groups and technical processes inaddition to employees of this library.The research also drives at identifying the informative services presentedby the library for those beneficiaries from the scientific research field, definingtheir fundamental characteristics as well, in addition to identifying the techniquesused in the library and its role in developing the scientific research and itsupgrade for a better future for Ain Shams University, our grand well-establisheduniversity